Legal Consequences of Third Party Resistance to Assets Encumbered with Mortgage Rights (Study of Decision Number 46/Pdt.Bth/2016/PN. Smr) - Rahmadiyanti, Dhiya Fitriyah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
Legal certainty is very important for every Indonesian citizen as a subject holding land rights, therefore the State must guarantee every rights holder to obtain legal protection as a certificate of proof of the rights they have and as strong and perfect evidence if a dispute occurs in the future. The purpose of this thesis research is to study the law on the resistance of third parties as holders of mortgage rights when viewed from the aspects of justice, legal consequences and legal certainty in Decision Number 46 / Pdt.Bth / 2016 / PN.Smr and How are the legal consequences of third party resistance to assets that are subject to mortgage rights when viewed from Decision Number 46 / Pdt.Bth / 2016 / PN.Smr. This study uses the Normative Juridical method. The data sources obtained are in the form of primary data sources and secondary data sources, namely Court Decisions and related Laws. This research was conducted by examining the Samarinda District Court Decision. The results of this study, when viewed based on the theory of justice, legal consequences and legal certainty, are fair enough for the winning party, but unfair for the third party as the holder of the Mortgage Right. The legal consequences for the third party are clearly disadvantaged because the third party is not allowed to file a third party objection. Viewed from the legal certainty side, the Panel of Judges has also not carried out legal considerations as its rights in a concrete manner because there are two references, so this creates a side of legal uncertainty.